2022
DOI: 10.3390/molecules27154903
|View full text |Cite
|
Sign up to set email alerts
|

Two New Phenolic Glycosides with Lactone Structural Units from Leaves of Ardisia crenata Sims with Antibacterial and Anti-Inflammatory Activities

Abstract: Two new lactones, named Ardisicreolides A–B (1–2), together with four known flavonoids, Quercetin (3), Myricetrin (4), Quercitrin (5), Tamarixetin 3-O-rhamnoside (6), were isolated from the ethyl acetate portion of 70% ethanol extracts of dried leaves from Ardisia crenata Sims. These compounds were identified from Ardisia crenata Sims for the first time. The structures of 1–6 were elucidated according to 1D and 2D-NMR methods and together with the published literature. All of the isolated compounds were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Two new compounds were obtained from the leaves of Ardisia crenata Sims (Pr laceae) and were named ardisicreolides A-B (68) (Figure 16) [114]. The new compo are similar to the known compound myrsinoside A, differing in the presence o A new farnesylindole alkaloid was obtained from the flowers of Anomianthus dulcis (Dunal) J. Sinclair (Annonaceae) and it was named (R)-3-(8 ′ -hydroxyfarnesyl)-indole (63) (Figure 15) [109].…”
Section: Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two new compounds were obtained from the leaves of Ardisia crenata Sims (Pr laceae) and were named ardisicreolides A-B (68) (Figure 16) [114]. The new compo are similar to the known compound myrsinoside A, differing in the presence o A new farnesylindole alkaloid was obtained from the flowers of Anomianthus dulcis (Dunal) J. Sinclair (Annonaceae) and it was named (R)-3-(8 ′ -hydroxyfarnesyl)-indole (63) (Figure 15) [109].…”
Section: Phenolsmentioning
confidence: 99%
“…Cabrera (Anacardiaceae) and named luteolin-(6→8″)-apigenin (76) (Figure 17), showing anti-inflammatory activity through its membrane-stabilizing effect on erythrocytes [119]. The Two new compounds were obtained from the leaves of Ardisia crenata Sims (Primulaceae) and were named ardisicreolides A-B (68) (Figure 16) [114]. The new compounds are similar to the known compound myrsinoside A, differing in the presence of the cinnamoyl and pentadactyl lactone rings and the configuration of the double bond of the cinnamoyl group.…”
Section: Flavonoidsmentioning
confidence: 99%
“…The NMR data of each component are attached in the appendix. These known compounds (Figure 1) were identified as myricetrin [15], myricetin [16], myricanol [17], epigallocatechin gallate [18], and taraxerol [19] by comparison of the spectral data with the published literature. The structure of 11-O-acetylmyricanol was determined by mass spectrometry, carbon spectrum, hydrogen spectrum, COSY, HMBC, DEPT, HSQC, and NOESY (Supplementary materials).…”
Section: Purity and Structure Identification Of Hsccc Peak Fractionsmentioning
confidence: 99%
“…It also has high medicinal value. Lactones extracted from its leaves have great antibacterial and anti-inflammatory activities [34]. Studies on A. crenata showed that it contained a variety of saponins or medicinal components showing good healing ability for a variety of diseases [35].…”
Section: Introductionmentioning
confidence: 99%